Editorial: self‐dilation for refractory oesophageal strictures is worth considering—author's reply. Issue 2 (25th June 2018) - Halland, M.
Abstract : Linked Content This article is linked to Qin et al and Heading papers. To view these articles visithttps://doi.org/10.1111/apt.14807 andhttps://doi.org/10.1111/apt.14838 .